The importance of screening for lung cancer. (October 2014) - Horeweg, Nanda; de Koning, Harry
<x xml:space="preserve">Abstract</x> Lung cancer is a major public health problem as it causes the most cancer-related deaths worldwide. As the disease often causes no symptoms at early stages, diagnosis at advanced stages, wherein cure is no longer possible, is common. Improvements in lung cancer treatment have been made, but yielded only modest improvement in survival over the last decades. Continuous efforts should be made to force back exposure to causative agents of lung cancer, tobacco smoking in particular. However, this is not expected to reverse the lung cancer epidemic in the next decades. Lung cancer screening can reduce morbidity and mortality by detecting lung cancer at an early and curable stage. Initial estimates of many harms and benefits of screening have been made, suggesting that the benefits of low-dose computed tomography screening outweigh the harms. Finally, the success of an implemented screening program is determined by the benefit it will yield for public health.